“On stage, everyone loves a Black”: Afro-Ukrainian Folk Fusion, Migration, and Racial Identity in Ukraine - Helbig, Adriana (Current Musicology, 2011)
In the harsh snowy days of late November, 2004, I joined hundreds of thousands of Ukrainian citizens on Maidan Nezalezhnosti, Independence Square in Kyiv, to protest the unfair presidential election which had been rigged in favor of the corrupt government -sponsored candidate. I was there as an international election observer and was simultaneously researching the role that Ukrainian-language popular and folk music were playing in the protests, dubbed as the Orange Revolution (Helbig 2006). Music has had such a long history of politicization in Ukraine that newspapers printed the names of Ukraine’s most well-known musicians and the candidate they supported, either the opposition candidate or the government -sponsoredone (Klid 2007). These affiliations were based less on political ideology as they were ruled by ethnic identity, language choice between Ukrainian and Russian, regional identity, and religious identity. Among the performers on Maidan Nezalezhnosti were an African-Jamaican duo calling themselves “Chornobryvtsi” (Black -Browed), performing Ukrainian folk songs dressed in Ukrainian folk garb for the crowd. The passion with which the crowd embraced Chornobryvtsi made it clear that outsider validation of Ukrainian ethnic identity and culture was at the root of the protests. The crowds’ chants of “Chor-no-bryv-tsi! Chor-no-bryv-tsi!” signaled an embrace of nonUkrainians who supported Ukrainian language and culture, perceived by protestors to be under threat by the Russian -oriented policies of the political regime. The role of African and Jamaican musicians in that critical historical moment also brought forth the role of migrants and foreigners living in Ukraine in Ukraine’s ongoing political and cultural identity struggles, in terms of its vacillating leanings between more pro-Russian and pro-Western ideologies and policies. Since the 2004 Orange Revolution, the highly mediatized involvement of African musicians in Ukraine’s pop-folk music scenes has broadened the contemporary public sphere beyond the ongoing ethnic Russian and ethnic Ukrainian culture wars since Ukrainian independence in 1991. The continued popularity of African musicians helps foreground issues of pluralism and multiculturalism that reinforce the notion of Ukraine as a patchwork quilt made up of many different ethnic, religious, and linguistic groups, including ethnic Russians, Russian-speaking Ukrainians, ethnic Ukrainians, Crimean Tatars, Roma ( Gypsies), Armenians, and Jews. African folk musicians’ appearances on talk shows, at folk music festivals, at public city events, in newspapers and on the Internet, have influenced the ways that people speak about ethnicity and race, albeit with a greater sense of conflation of identities as regards people with dark skin. It is common for locals to refer to musicians from Africa as African American or to use “African” and “African American” or “Afro-American” interchangeably when speaking or writing about performers from the African continent in the media. Musicians from Africa capitalize upon the popularity of u.s. popular music genres associated with African Americans, conflating the widely marketed stereotype of “African American as musician” to localize their social acceptance via Ukrainian folk music idioms. Are Africans accepted in their own right or only to the extent that they adhere to more localized cultural norms, such as participation in Ukrainian folk-influenced music? How do Soviet -era and contemporary attitudes regarding Africans and African Americans influence levels of inclusion for African migrants in post-Orange Revolution Ukraine?